Mengembangkan Sosial Emosional Anak Melalui Metode Bercerita - Khadijah Khadijah; Hairani Ananda Putri; Annisa Fitri Akhiriyah; Annisa Zakia Nasution; Evi Sukma Pratiwi; Miftahul Jannah Harahap; Novia Rahmawati (Universitas 45 Surabaya, 2024)
Emotional maturity is the maturity of a person's ability to regulate and process emotions so that they are able to provide effective responses to situations that arouse emotions. Storytelling can support social and emotional development in children The aim of this research is to find out whether the use of storytelling methods is very effective in supporting social and emotional development in children.